Ecclesiastical bulletins as a source for the history of primary education in Spain (1851-1931) - Diego Pérez, Carmen; González Fernández, Montserrat (Historia y Memoria de la Educación, 2019)
Resorting to periodic publications in historical research has become common in recent decades; however, the information supplied by ecclesiastical bulletins — the broadcasting organ of the Catholic Church’s official directives— has not been used sufficiently as a tool for understanding the connections and relationships between the church and the state as regards teaching. This article aims to point out the potential that these bulletins have for education historians. In this regard, we first set out to synthesize the legal framework and the church’s doctrine — beginning with the birth of the periodic publication in the mid-19th century up to the third decadfe of the 20th century — and we outline the relationship that church and state maintained during this period. Then we characterize the ecclesiastical bulletins and take note of those educational issues related to primary education that are addressed in them and that would be useful, in some cases, to contrast and compare information that comes from other sources —the control that church and state exerted on the teachers in relation to the catholic practices that they should conduct with the students, for example— and, in others, to investigate little known aspects —the catholic teachers’ group of associations, as another example—, contributing, thus, to the construction of a more complete history of primary education.